2017
DOI: 10.31299/hrri.53.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Parent education in autism spectrum disorder - a review of the literature

Abstract: Obitelji koje žive s poremećajem iz spektra autizma suočavaju se s mnogim izazovima koji ne utječu samo na dijete s tim poremećajem i njegov razvoj, već i na funkcioniranje obitelji i kvalitetu njezina života. Edukacija roditelja o poremećaju iz spektra autizma identificirana je kao prioritetna intervencija u području ove problematike, kako na nacionalnoj, tako i na međunarodnoj razini. Dok je, s jedne strane, literature o osposobljavanju (treningu) roditelja u okviru specifičnih terapijskih pristupa opsežna, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
(47 reference statements)
3
14
0
6
Order By: Relevance
“…The other nding of the present study was that among 53 papers, only 14 articles were held in workshops and training forms; participants in this short term training model do not perform a speci c practice and they listen to the teacher only. However, this training model also have some bene ts for example, if the teaching protocols goal is increasing the theoretical knowledge and parents' awareness, this model can be used [23]. Ideally, it is expected that when the parents training is provided in a practical way along with using facilities such as video clips, their trainings and outcomes could be having more signi cant improvement [24]; however, in this study, the effectiveness percentage of mixed education (84.61) was higher than the only training method (78.57%).…”
Section: Discussionmentioning
confidence: 99%
“…The other nding of the present study was that among 53 papers, only 14 articles were held in workshops and training forms; participants in this short term training model do not perform a speci c practice and they listen to the teacher only. However, this training model also have some bene ts for example, if the teaching protocols goal is increasing the theoretical knowledge and parents' awareness, this model can be used [23]. Ideally, it is expected that when the parents training is provided in a practical way along with using facilities such as video clips, their trainings and outcomes could be having more signi cant improvement [24]; however, in this study, the effectiveness percentage of mixed education (84.61) was higher than the only training method (78.57%).…”
Section: Discussionmentioning
confidence: 99%
“…Rezultati ovog rada vidljivi u roditeljskim evaluacijama u skladu su sa sve većim brojem istraživanja koja potvrđuju korisnost programa koji se temelje na roditeljskom modelu i na roditeljskoj primjeni znanja o stvaranju prilika za učenje u djetetovoj svakodnevici kroz uobičajene rutine (Woods, Kashinath, 2007;Preece, Trajkovski 2017). Dobiveni rezultati i iskustva stečena tijekom provedbe programa potkrepljuju važnost činjenice da su roditelji i drugi članovi obitelji učinkoviti u poučavanju djece s razvojnim poteškoćama, jer je interakcija roditelj -dijete glavni pokretač rasta i razvoja u ranom djetinjstvu.…”
Section: Analiza Evaluacijskog Upitnika Za Roditeljeunclassified
“…The authors recommended broader feasibility evaluation, with a focus on accessibility, cultural appropriateness and scalability (Dawson-Squibb et al, 2018). Two further articles more extensively reviewed PET programmes (Prata, Lawson, & Coelho, 2018; Preece & Trajkovski, 2017). The review by Preece and Trajkovski (2017) identified 12 relevant studies, presumably as a result of narrowly focusing on a specific aspect of PET.…”
mentioning
confidence: 99%